Analisis Makna Simbolik dan Konteks dalam Puisi “Kangen” karya W.S. Rendra - Aena Zahro; Sophia Rahmawati (DEIKTIS: Jurnal Pendidikan Bahasa dan Sastra, 2025)
This study aims to analyze the symbolic meaning and emotional context in the poem "Kangen" by W.S. Rendra. The poem depicts a deep longing and soul-wrenching loneliness experienced by the poet due to the absence of a loved one. Through the use of figurative language such as metaphor, hyperbole, and repetitiBNon, Rendra illustrates longing as an inner torment that affects the thoughts, soul, and feelings of the poem’s "I" character. Symbolism like "a stove without fire" represents a state of emptiness and uselessness of the soul without the presence of the beloved. The emotional context of this poem highlights sadness, loneliness, and bitterness experienced by the poet, while also showing how longing can become a poison that dominates the blood and mind. This study employs a descriptive-analytical method with a literary approach to reveal the depth of meaning and emotional expression in the poem. The analysis results show that the poem "Kangen" is not merely an expression of longing but also a psychological and symbolic reflection on the suffering caused by unfulfilled love.